Interdisciplinary approach to the study of the history of the Caucasus region - Serobyan, Susanna (History and Culture, 2026)
In the past century and at the beginning of the 21st century, new disciplines were formed in historical science, conditioned by the use of new research approaches, principles and methods. The combination of the latest scientific approaches ensures the comprehensiveness of historical studies, creating an opportunity to study the past of societies from different perspectives and predict the future. In the article, the author discusses the necessity of applying an interdisciplinary approach to the study of local history, using the example of the Caucasian region. The author concludes that, at the present stage, a complex, in-depth, objective, and comprehensive study of the history of the Caucasus is impossible without an interdisciplinary understanding of historical events and phenomena. Only through such an approach is it possible to obtain objective scientific results, expand the boundaries of historical cognition, and form a complete and generalized scientific understanding of the Caucasian region’s role in world civilization.